Effect of University of Wisconsin organ-preservation solution on haemorheology. - van der Plaats, A; 't Hart, N; Morariu, A; Verkerke, G; Leuvenink, H; Ploeg, R; Rakhorst, G (2004)
In conventional cold-storage organ preservation, the donor organ is flushed with University of Wisconsin (UW) solution at 0-4 degrees C. The initial flush is used to wash out blood from the microcirculation to allow optimal preservation with the UW solution. The component hydroxyethyl starch (HES) of UW is known to cause relatively high viscosity and a possible interaction with blood, i.e. increased red blood cell (RBC) aggregation. The aim of this study was to investigate the influence of the HES component on the viscosity of UW and the aggregation behaviour of blood during washout. Viscosity aspects were measured with a cone-plate rheometer. HES-induced RBC aggregation was studied by means of an optical aggregation measuring device. The experiments were carried out with rat whole blood and mixtures of rat whole blood with UW-solution and UW without HES (UWmod), at 4 degrees C. The viscosity of blood at 4 degrees C is two-times higher than at 37 degrees C; the UW/blood mixture at 4 degrees C is 1.3-times more viscous than blood at 37 degrees C; the 4 degrees C UWmod/blood mixture equals the viscosity of blood at 37 degrees C. The UW/blood mixture shows a ninefold increased aggregation compared with whole blood. These aggregates are larger than the diameter of the sinusoids in the rat liver. A mixture of whole blood and UWmod shows a lower aggregation than blood. Apart from an increased viscosity, HES in UW causes increased RBC aggregation. The aggregates are larger than the diameter of the sinusoids. Initial washout could be optimised by pre-flushing to improve the viability of the liver and to decrease delayed graft function.